Michelia citrata (Noot. & Chalermglin) Q. N. Vu & N. H. Xia (Magnoliaceae Juss.), a new record for flora of Vietnam - Nam, Vu Quang; NIAN-HE, XIA (Academia Journal of Biology, 2012)
During the study on taxonomic revision of the family Magnoliaceae from Vietnam, we found a newly recorded species Michelia citrata (Noot. & Chalermglin) Q. N. Vu & N. H. Xia, which was first described as Magnolia citrata Noot. & Chalermglin in the Blumea (Blumea 52: 559. 2007). The speciess specimens were collected from the Kon Ha Nung experimental station, Kbang District, Gia Lai Province with their collection numbers of Nam 210111.3 (IBSC, VNF) and Tran Van Tien TVT 72008 (VNF). Michelia citrata (Noot. & Chalermglin) Q. N. Vu and N. H. Xia is most closely related to M. tonkinensis in their remarkable few (equal or less than 10) carpels, but can be distinguished from the latter by its carpes globose or subglobose (vs. ellipsoid), bigger size (3.5-7 3-3.5 cm vs. 2.5-3.5 1.5-2.5 cm), leaf blade broadly elliptic (vs. obovate to elliptic-obovate), larger size [(13-18(-23) 6.7-10.5(-13.5) cm vs. 7-11 5-5.5 cm)] and more numerous secondary veins (10-14 vs. 7-10 ). The vernacular name is called “Giổi xanh quả to” to refer its big and globose fruits. With this new record, the total Michelia species in Vietnam is heretofore estimated ca. 22 species.